Knowledge, attitudes and perception on reproductive health education among secondary school children in Kinta District, Perak D. R., 1995 - Marina Ab. Hamid; Jamal Hisham Hashim (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional survey was conducted in Kinta District, Perak Darul Ridzuan. The aim of the survey is to identify adolescents' level of reproductive health knowledge, attitude towards pre marital sex and their perception towards sex education/ adolescent health in school. Stratified random sampling was canied out among form 4 government secondary schools attendees. A total of 204 respondents completed selfadministered questionaires. The proportion of respondents were equally distributed by sex. A total of 50% were Malays, 52% were from urban schools and 65% were from co-educauona1 schools. Generally results indicated that reproductive health knowledge was lacking. Statistically, there was significant difference between knowledge by sex and type of school (p <0.05). A total of 16.7% approved of pre marital sex, 25% were uncertain and the rest disapproved of pre marital sex. However 46% disagreed that religion has influence on their behavior towards pre marital sex. Statistically attitude differs significantly by sex and ethnicity (p <0.05). However there was insignificant correlation between knowledge and attitude. Sex and ethnicity were the only significant predictive factors for pre marital sexual activity (p<0.05). Majority perceived the needs of sex education in school and felt that the current curriculum as insufficient. Books, peer and pornographic video were among the common sources of information. Hence sex education plays an important role in conveying reliable source of information.